Pengaruh Pendistribusian Zakat Produktif terhadap Tingkat Pengurangan Kemiskinan Mustahik di Kota Banjarmasin - Rizqa; Muhammad Yassir Fahmi; Mochammad Arif Budiman (P3M Politeknik Negeri Banjarmasin, 2021)
One of the instrument trusted to decrease poverty is zakat especially if distributed to productive activities. This research aimed to find out if the distribution of productive zakat has effect on the decrease level of mustahik poverty, to find out total and classification of mustahik households and the change of mustahik households without and with productive zakat. This research used correlative quantitative method with analysis technique of simple linear regression and CIBEST analysis. This research used saturated sample technique to mustahik of Amil Zakat Board (BAZNAS) of Banjarmasin City with a total of 23 respondents. From the research results, it can be concluded that the distribution of productive zakat has no significant effect decreasing on the poverty level of mustahik. This can be seen from the t count (-1,177) < t table (2,079) and from F count (1,385) < F table (4,30) p value (Sig) in the amount of 0,252 > 0,05 which means that Ho is accepted. Based on total households of mustahik based on CIBEST quadrant before and after the presence of productive zakat fund, there is difference of classification of each mustahik household. The condition change of mustahik household without and with productive zakat fund based on material and absolute poverty index each experienced decrease in the amount of -10,5 and -100%. Spiritual poverty index does not change at all either before or after accepting productive zakat in the amount of zero percent. While prosperity index increase to 504,7%.